MAN-MADE IMPACT AND WATER CYCLE RATES IN CENOMANIAN-CALLOVIAN GROUNDWATER COMPLEX (KYIV) - Koshliakova, T.; Koshliakov, O.; Dolin, V.; Skrypkin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with estimating water cycle rates for the Cenomanian-Callovian groundwater complex located within Kyiv hydrologic system, namely – evaluating velocity of surface water entry to the groundwater complex and its share in groundwater budget. The research is carried out mostly via a water balance method, and a hydrodynamic method, alongside with testing tritium activity in water samples from the Cenomanian-Callovian groundwater complex, and processing proper isotope data from radio-geologic and radiochemical analysis. To build cartographic schemes ArcGIS program was used. The paper gives an overview of the data published earlier on water cycle rates within Kyiv groundwater system, which functions under maninduced impact, and determines a portion of atmospheric precipitations in the Cenomanian-Callovian groundwater complex. Taking into account anthropogenic load in water cycle rebuilding of the hydrodynamic system, there were determined estimates for the time water passes through the upper Cretaceous malm-chalk thickness; the latter is the upper confining layer for the groundwater complex under consideration. The research proves the presence of tritium in groundwater to equally result from both natural and man-caused factors, these two both affecting the process of vertical underground water cycle formation. For the first time ever, using isotope radio-geologic and radiochemical data, water balance, and hydrodynamic values it was determined that the portion of infiltration supply in the Cenomanian-Callovian groundwater complex, which provides sources for Kyiv area, is equal to 21-23%, and the arrival time of surface water to the groundwater complex under consideration is equal to 10-12 years. The data obtained allow for determining water cycle rates in the Cenomanian-Callovian groundwater complex as well as immunity of potable ground water. The methodology that combines water balance, hydrodynamic methods, and isotope radio-geologic and radiochemical analysis can be successfully applied when estimating water cycle rates for other areas.
Keywords: groundwater; water cycle; isotope radio-geologic and radiochemical data; water budget; immunity